2018
DOI: 10.1186/s41938-017-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some plant growth-promoting rhizobacteria strains on root-knot nematode, Meloidogyne incognita, on tomatoes

Abstract: Root-knot nematode, Meloidogyne incognita, is one of the main problems in vegetable-growing regions, decreasing yield quality and quantity worldwide. Root-knot nematode management tactics mostly involve chemical control which is a threat to the environment, consequences to human health. Biological control of nematodes is considered to be one of the best alternatives to the chemical control. In this study, the effect of some bacterial isolates against M. incognita was determined on tomato in the greenhouse. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 18 publications
1
17
0
2
Order By: Relevance
“…), phosphate solubilization, siderophore production, nitrogen fixation and protection towards different pathogenic organisms including PPNs [20,21]. The PGPR mediated plant resistance towards PPNs is provided by production of various antagonistic compounds, lytic enzymes, toxins and antibiotics that inhibit the nematode proliferation or directly killing them [22]. Moreover, PGPR also colonises the plant roots in the rhizosphere, produces various metabolites and their by-products that either affect the motility of PPN, or their emergence and penetration within the plant roots [23].…”
Section: Introductionmentioning
confidence: 99%
“…), phosphate solubilization, siderophore production, nitrogen fixation and protection towards different pathogenic organisms including PPNs [20,21]. The PGPR mediated plant resistance towards PPNs is provided by production of various antagonistic compounds, lytic enzymes, toxins and antibiotics that inhibit the nematode proliferation or directly killing them [22]. Moreover, PGPR also colonises the plant roots in the rhizosphere, produces various metabolites and their by-products that either affect the motility of PPN, or their emergence and penetration within the plant roots [23].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly P. polymyxa strain GBR-1 reduced egg hatching and population of M. incognita (Khan et al 2008). Based on a study performed by Cetintas et al (2018) among 15 bacterial strains studied, 2 strains of Paenibacillus castaneae and 2 strains of Mycobacterium immunogenum were identified as the best promising biocontrol agents for the management of M. incognita. Prevention of egg hatching is one of the mechanisms to emerge resistance against RKNs by plant growth-promoting bacteria.…”
Section: Impact Of Pgpr To Reduce the Nematode Contamination Of Tomatmentioning
confidence: 99%
“…Batool et al (2013) have reported that the strain P. aeruginosa caused more than 90% mortality in in vitro tests, performed with M. javanica, due to the high secretion of chitinase. Cetintas et al (2018) reported that, among 15 studied bacterial strains, the strains Paenibacillus castaneae and Mycobacterium immunogenum are found to be best biocontrol agents for management of the nematode Meloidogyne incognita.…”
Section: Discussionmentioning
confidence: 99%